Exposure to omentum adipose tissue conditioned medium from obese pregnant women promotes myometrial artery dysfunction. Issue 1 (13th October 2017) - Hayward, Christina E.; Cowley, Elizabeth J.; Sibley, Colin P.; Myers, Jenny E.; Wareing, Mark
Abstract: Aim: Underlying mechanisms of poor pregnancy outcome in obese (OB) mothers (body mass index [BMI] ≥ 30 kg/m 2 ) are unknown. Our studies demonstrate that OB pregnant women have altered myometrial artery (MA) function related to the thromboxane and nitric oxide pathways. In obesity, increased central fat mass is associated with an altered endocrine milieu. We tested the hypothesis that in OB pregnant women the omentum, a central fat store, releases factors that promote dysfunction in normal MAs. Methods: Myometrial and omental adipose tissue biopsies were obtained from women with uncomplicated term pregnancies. Omental adipose tissue explants from six normal weight (NW; BMI 18.5–24.9 kg/m 2 ) and six OB (BMI ≥ 30 kg/m 2 ) women were cultured and the conditioned medium collected and pooled to produce NW medium and OB medium. Adipokine concentrations were measured using enzyme‐linked immunosorbent assays. Wire myography was used to assess the effect of conditioned medium (NW or OB; N = 7) or leptin (100 nM; N = 5) exposure on MA responses to U46619 (thromboxane‐mimetic) and bradykinin (endothelial‐dependent vasodilator). Results: OB medium had higher leptin and lower adiponectin levels than NW medium. U46619 and bradykinin concentration response curves shifted upwards in MAs exposed to OB medium but were unaffected by leptin. Conclusions: Omental adipose tissue from OB pregnant women produced altered concentrations of adipokines. Acute OB medium exposure induced MA dysfunction, an effect not mirrored by exposure to leptin. These data suggest that an aberrant endocrine environment created by increased central adiposity in OB pregnant women induces vascular endothelial dysregulation, which may predispose them to a poor pregnancy outcome.